2021
DOI: 10.1021/acssuschemeng.1c04875
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly, Highly Efficient Ethanol-Assisted Supercritical Preparation of an Ultrathin ZnO Nanotube

Abstract: The nanotubes widely used in the advanced semiconductor manufacturing field suffer from complicated timeand energy-consuming synthesis processes, thus requiring an efficient preparation method. In this study, ethanol-assisted supercritical treatment (SC-EA), a sustainable approach with less environmental hazard, has been applied to efficiently synthesize ZnO nanotubes. Materials free from any detrimental effect on the environment have been utilized in the proposed ethanol−water mixed supercritical fluid techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Therefore, ZnO nanoarrays have become one of the key materials in the field of optoelectronics [ 16 , 17 , 18 , 19 ]. Many methods have been used to synthetize ZnO nanoarrays, such as chemical, electrochemical, and physical deposition techniques [ 20 , 21 , 22 , 23 ]. Some studies have shown that the photoelectric properties of ZnO nanoarrays are closely related to the morphology of one-dimensional ZnO nanostructures (including nanowires, nanobelts, nanotubes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ZnO nanoarrays have become one of the key materials in the field of optoelectronics [ 16 , 17 , 18 , 19 ]. Many methods have been used to synthetize ZnO nanoarrays, such as chemical, electrochemical, and physical deposition techniques [ 20 , 21 , 22 , 23 ]. Some studies have shown that the photoelectric properties of ZnO nanoarrays are closely related to the morphology of one-dimensional ZnO nanostructures (including nanowires, nanobelts, nanotubes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Nanotubes have been a popular one-dimensional allotropic form of carbon in the scientific domain. Currently, a wide variety of nanotubes composed of various different elements, such as carbon, titanium, tungsten, zinc, etc., have attracted the attention of scientists [1][2][3][4]. It has been established that a wide range of layered materials can form nanotubes since the discovery of nanotube morphology [5].…”
Section: Introductionmentioning
confidence: 99%